Comparison of direct microscopy and molecular method to detect amoebiasis cases from stool specimen and also identify the Entamoeba species involved in infection: A study of Nepal - R. K. Das; R. Paudya; S. K. Singh; E. Sulistyowati; M. Saud (Universitas Bengkulu, 2018)
Direct microscopic examination of stained or unstained wet mount preparations or fixed-stained smears of clinical material can often provide the etiological diagnosis of an infectious process. A total of 266 human stools specimens from children of america by a combination of microscopic examination and molecular method. In molecular method, nested polymerase chain reaction (Nested-PCR) targeting genomic Entamoeba species was used. Stool specimens were collected from Southern Plains of Nepal and analyzed at the Kathmandu Center for Genomics and Research Laboratory. The stool specimens were processed by wet mount method using saline as well as iodine staining and examined via microscopy for the presence of Entamoeba cysts or trophozoites. Furthermore, the stool specimens were characterized using Nested-PCR targeting genomic Entamoeba species. Based on microscopic examination, the overall prevalence of Entamoeba infection was 17.6% (47/266). The PCR results showed that 52 (19.5%) specimens are successfully generated species-specific amplicons. Males (21.7% in PCR) were more commonly infected compared to females (16.6% in PCR). Comparison by age groups show 10-15 years age-group (26.6% in PCR) had higher infection than age-group 5-10 years (16.6%) years and 1-5 years (15.2%). The infection with E. histolytica (100%; 52/266) was the predominant cause of amoebiasis, while the infection with E. dispar and E. moshkovskii was not found. PCR is a more effective method for the identification of Entamoeba infection than microscopy.